On the Problem of Dating the Group of Bosporan Watercolor Pelikai in the Collection of the State Hermitage - Mogilevskaya, Ekaterina V. (Actual Problems of Theory and History of Art, 2012)
The article deals with the group of Bosporan so-called watercolor pelikai held by the State Hermitage Museum and is mostly concerned with the problem of their dating. Earlier scholars who studied these items did not draw sufficient attention to this problem. The author joins the opinion that archaeological context is very important in the research of this kind, yet it is with the help of methods of art historical analysis that the date of watercolor pelikai can be clarified and defined more precisely.